Emerging Labour Strategies in Toronto’s Hotel Sector: Toward a Spatial Circuit of Union Renewal - Tufts, Steven (Environment and Planning A: Economy and Space, 2007)
I discuss the recent union renewal strategies adopted by UNITE-HERE Local 75, the union representing a majority of Toronto’s organized hotel workers—a fragmented and diverse labour force. Local 75’s renewal strategies are multiscalar with knowledge and resources flowing through the organization forming a spatial circuit of union renewal. Conceptualizing union renewal as a spatial circuit maps the interdependencies of different scales of labour organization and the tensions that emerge among such scales. The paper focuses on the hotel union’s strategic attempts to (re)create pattern bargaining at local and international scales and organize new hotels prior to their construction. I conclude with a brief discussion linking the recent merger of UNITE-HERE and its departure from the AFL-CIO to broader renewal processes.